The Impact Of Social Media On Banks In Russia Phenomenological Study - Larchuzhenkova, Nadezhdathe (2010)
Social Media, or Web 2.0, is phenomenon that invades in life of people and organizations and has created a permanent shift in communication and interaction processes where they participate in. Experiencing the growing power of the internet technologies and social media impact, many companies from different industries around the world have started rethinking and redesigning the communication processes. However, although financial institutions are generally perceived as technological innovators (MarketingSherpa, 2003), their current engagement in Web 2.0 is poor (Wetpaint & Altimeter Group, 2009). TOP managers of many banks still doubt in reality of social media impact on their business and perceive Web 2.0 as environment for entertainment, rather than strategic communication tool. Yet, irrespective of companies‟ engagement in Web 2.0 communication, the information flow surrounding each organization is present in social media (Solis, 2010). Being the extent of Word-of-mouth (WoM) communications, social media influences consumers‟ attitude towards organizations, customers‟ perception about superiority of companies‟ products and services and determine people‟s buying decisions. Therefore, some banks from developed countries have begun to experiment with social media. Yet, the current study concentrates on Russian banks as representatives of the financial industry of developing countries as Web 2.0 in the latter reminds less researched topic. To understand Web 2.0 positive and negative impact on Russian banks, the shift from traditional communication model towards new communication paradigm was examined, following by the investigation of changes of consumers‟ profiles of different generations. Next, with the assistance of thirteen high-ranking and TOP-level managers from banks, agencies providing Web 2.0 services and Web 2.0 experts, the phenomenological study was prepared. The data collected from the participants were analyzed through systematic steps of transcendental approach to phenomenology (Moustakas, 1994) to provide the composite description answering the phenomenological questions attributed to the research aims. Findings revealed that although there are several banks in Russia, which integrated in Web 2.0, many TOP-managers still doubt in presence of social media phenomenon.